Health care - Ferguson, Olivia (Issues that concern you, 2011)
"Health Care: Health Care Reform Will Help America's Economy; Health Care Reform Will Cause a Rise In Unemployment; Health Care Reform Would Give the IRS More Power; The IRS Does Not Have the Power to Enforce a Health Care Mandate; Americans Want Univer